The Employment Experience of Recent Graduate Education Students - Decore, Anne Marie (Canadian Journal of Higher Education, 1992)
Because it both employs a significant portion of university graduates and provides an early warning of future demand for higher levels of education, the teaching profession affords an instructive illustration of the experiences of highly trained personnel in the labour market. The study is an attempt to elucidate part of the picture of supply and demand for teachers by examining the labour market experiences of recent education graduates of the University of Alberta. Although concern recently has surfaced that a shortage of teachers is imminent, these respondents who entered the labour market in late 1987 or mid-1988 reported that teaching jobs were still in short supply in early 1989. Only 62 percent found full-time employment, though 86 percent sought teaching jobs. Job location, age and the extent of the job search emerged as important influences on employment status.